DAS POTENZIAL KOLLEGIALEN FEEDBACKS FÜR DIE FÖRDERUNG DER EVALUATIONSKOMPETENZ BEI ANGEHENDEN FREMDSPRACHENLEHRENDEN – ERGEBNISSE EINER STUDIE - Janicka, Monika (Neofilolog, 2020)
The article introduces formative assessment as one of the most powerful factors influencing students’ achievements and presents its significance for process-oriented learning and teaching. Due to its importance formative assessment should be an inherent part of the pre-service teacher training program. The aim of the present paper is to highlight the potential of peer-to-peer-feedback, as a part of formative assessment, for enhancing the assessment competence of pre-service teachers. The results of the study presented in the article suggest ways in which peer-to-peer feedback can be used to foster the assessment competence of prospective teachers.